2012
DOI: 10.1021/np300016r
|View full text |Cite
|
Sign up to set email alerts
|

Peptidolipins B–F, Antibacterial Lipopeptides from an Ascidian-Derived Nocardia sp.

Abstract: A marine Nocardia sp. isolated from the ascidian Trididemnum orbiculatum was found to produce five new lipopeptides, peptidolipins B-F (1–5), which show distinct similarities to the previously reported L-Val(6) analog of peptidolipin NA. Synthetic modification of peptidolipin E (4) was used to determine the location of an olefin within the lipid chain. Advanced Marfey’s method was used to determine the absolute configurations of the amino acids. Peptidolipins B (1) and E (4) demonstrated moderate antibacterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 33 publications
1
35
0
Order By: Relevance
“…33 To date, no natural products of this type have been reported with an S configuration at the β -acyloxy carbon, although NMR properties for the peptidolipin B have been predicted via DFT calculations (see Figure 4). 35 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…33 To date, no natural products of this type have been reported with an S configuration at the β -acyloxy carbon, although NMR properties for the peptidolipin B have been predicted via DFT calculations (see Figure 4). 35 …”
Section: Resultsmentioning
confidence: 99%
“…As noted above, this strategy has been successfully used by others, although such an analysis failed during the evaluation of the peptidolipins. 35 As described below, Mosher's method was tenuous for the kailuins and motivated the quest for back-up analysis. This was achieved by assembling a minidatabase of 13 C NMR chemical shift values.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, during 2012–2013, the novel marine lipopeptides, peptidolipins B–F (MIC = 64 μg/mL), were isolated from an ascidian-derived Gram positive Nocardia sp. bacterium [116]. …”
Section: Marine Compounds With Antibacterial Antifungal Antiprotmentioning
confidence: 99%
“…WMMB 215 isolated from ascidian Trididemnum orbiclatum. These compounds showed bacteriostatic activity agaisnt MRSA and MSSA (methicillin sensitive Staphylococcus aureus) (Wyche et al 2012). Analysis of the NRPS sequences with registered protein in the NCBI database confirmed that the NRPS gene of isolate DR-2R-115-35 has similarity to the genus Streptomyces.…”
Section: Discussionmentioning
confidence: 77%